(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
This work develops from the archaeological researches carried out between 2002 and 2008 in Rome, via Labicana, in the area of “G. Carreca” and “Ce.Ri.co.” barracks. These the phases recognized: late Flavian, Antonine and Severiane, before the latest in the second half of IV/V cent. A.D. The survey focus on a considerable marble’s deposit in the kind of pavimental and parietal opus sectile. It’s a mark of an elevated customer and it represents a decorative shapes set of samples in use at Rome between I and IV-V cent. A.D.